Reinterpreting Qur'anic Themes: Muṣṭafa Muslim's Approach to Mauḍū'ī Tafsir - Farhan, Rivki Lutfiya; A. Sabiqul Himam; M. Abdul Ghofur (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
This article delves into Muṣṭafa Muslim's method of mauḍū'ī tafsir, emphasizing the process of reinterpreting themes found within the Qur'an. The research methodology employed is library-based, utilizing an analytical framework. It commences with identifying primary sources pertinent to the research focus, particularly literature concerning Qur'anic interpretation, with a specific emphasis on the mauḍū'ī approach. The primary focus lies on Muṣṭafa Muslim's work "Mabāhits fī al-Tafsīr al-Mawdhū'ī." Through this investigation, it is evident that Muṣṭafa Muslim developed three distinct methods for crafting a distinctive mauḍū'ī interpretation. Firstly, he employs a technique to delve into the meanings of specific Qur'anic words. Secondly, he employs a method to identify and analyze themes present within individual Qur'anic surahs. Lastly, he utilizes an approach to explore themes spanning across various surahs in the Qur'an. By examining Muṣṭafa Muslim's approach to understanding and reinterpreting Qur'anic themes within the context of mauḍū'ī tafsir, this article offers valuable insights for researchers and enthusiasts of Qur'anic studies, thereby paving the way for further scholarly exploration in this domain. Contribution: This research enriches the study of mauḍū'ī tafsir by analyzing Muṣṭafa Muslim's method of systematically interpreting Qur'anic themes.